12. APPLICATION OF GENETIC DECODING FOR PROACTIVE NUTRITIONAL SELECTION FOR HEALTH CARE (Vietnam Journal of Community Medicine, 2025)
Objective: The study aims to clarify the relationship between genes and nutrition, enabling the selection of personalized diets and the proactive application of health care strategies from the time of good health, before the onset of any illness.Method: Synthesizing and analyzing published domestic and foreign studies on the relationship between genes and nutrition, genetics related to health indicators such as BMI, digestive ability, risk of diabetes, obesity, cardiovascular disease.Results: Gene decoding helps determine how each person's body reacts to food, from digestive ability to the risk of chronic diseases such as diabetes, obesity and cardiovascular disease. Studies show that people who adjust their diet according to genetic information can reduce the risk of disease.Conclusion: The application of genetic decoding in nutrition emphasizes the role of genetic decoding in personalizing diet for proactive health care.
Keywords: genetic decoding; proactive health care; nutrition